A IMPORTÂNCIA DA MÚSICA NA FORMAÇÃO DO INDIVÍDUO: UMA REFLEXÃO SOBRE OS OBSTÁCULOS DA DIFUSÃO DA EDUCAÇÃO MUSICAL NO ESPAÇO ESCOLAR - Pereira, Ivan Nunes (2014)
This study investigated the interactions between music and mathematics, considering experiences and reflections of exponents of the exact sciences, with their range of musical concepts, ratios and proportions, consonance, harmony, temperament, harmonic series, which contributed to the structuring of the art of music as a science. In light of this science of music through descriptive analysis Music, told the story of a country that, according to PISA, remained in the rankings of education since 2010 to 2012, revealing interdisciplinary interactions of science and the concepts of analogical thinking, advocated by Levy and Machado and the theory of multiples intelligences by Gardner. Finally, it was proposed to reflect on the importance of music education in shaping the individual and on barriers to its diffusion within the school.